Influence and Green's functions for orthotropic micropolar continua (Archives of Mechanics - Test, 2002)
The article reports on a methodology to synthesize the response of orthotropic micropolar half-space subjected to concentrated and distributed loads. The disturbance due to normal and tangential loads are investigated by employing the eigenvalue approach. The integral transforms have been inverted by using a numerical technique to obtain the normal displacement, normal force stress and tangential couple stress in the physical domain. The results concerning these quantities are given and illustrated graphically.